Voices of the Weak: Music and Minorities. Zuzana Jurková & Lee Bidgood (eds.): Prague: NGO Slovo 21 & the Faculty of Humanities, Charles University in Prague, 2009, 250 pp + 1 accompanying CD, ISBN 978-80-254-4095-7. - Seidlová, Veronika (Lidé města, 2009)
A review of the book by Zuzana Jurková and Lee Bidgood.